2018
DOI: 10.48048/wjst.2019.4046
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Medication Adherence Scale for Persons with Coronary Artery Disease (MAS-CAD): A Nursing Perspective

Abstract: The purpose of this study was to develop a Medication Adherence Scale for Persons with Coronary Artery Disease (MAS-CAD) based on a nursing perspective. This study was guided by scale development procedures, which consisted of 7 steps: 1) clarifying and determining the concept, 2) generating an item pool, 3) determining the format for measurement, 4) reviewing the initial item pool by 7 professional experts, 5) conducting preliminary item pilot study with 30 Thais with CAD, 6) conducting field-testing for psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Two asked about intentional reasons only [ 74 , 120 ] and one [ 73 ] asked about unintentional reasons only. Group-3: items asks about both the extent of, and reasons for, non-adherence [ 45 , 50 , 54 56 , 65 , 67 , 77 , 78 , 81 , 85 , 89 , 91 93 , 95 , 98 , 103 , 110 , 113 , 114 , 117 , 126 ]. Six MA-PROMs [ 50 , 54 , 81 , 92 , 93 , 98 ] in Group-3 were comprehensive enough to capture information on the extent of both medication-taking and prescription-filling and at least two additional domains from both intentional and unintentional reasons for non-adherence from the MAM framework [ 40 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two asked about intentional reasons only [ 74 , 120 ] and one [ 73 ] asked about unintentional reasons only. Group-3: items asks about both the extent of, and reasons for, non-adherence [ 45 , 50 , 54 56 , 65 , 67 , 77 , 78 , 81 , 85 , 89 , 91 93 , 95 , 98 , 103 , 110 , 113 , 114 , 117 , 126 ]. Six MA-PROMs [ 50 , 54 , 81 , 92 , 93 , 98 ] in Group-3 were comprehensive enough to capture information on the extent of both medication-taking and prescription-filling and at least two additional domains from both intentional and unintentional reasons for non-adherence from the MAM framework [ 40 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patient-reported outcome measures development was rated for the 24 original MA-PROMs [ 45 , 60 , 77 , 78 , 81 , 86 , 89 , 96 , 97 , 102 , 103 , 105 , 113 , 114 , 116 , 119 122 , 127 – 130 ] and 13 MA-PROMs [ 46 , 50 , 51 , 53 56 , 65 , 67 , 70 , 80 , 85 , 92 , 95 , 110 , 117 ] were modified versions of the original MA-PROMs. Patient-reported outcome measures development was not rated for 3 MA-PROMs [ 66 , 71 , 91 , 125 ], the development studies for two were published in a language other than English [ 71 , 91 ], and a development study could not be found for one [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations